RESPON PERTUMBUHAN TANAMAN BAYAM CABUT (Amaranthus tricolor L.) TERHADAP BEBERAPA MACAM MEDIA TANAM DENGAN MENGGUNAKAN POT BATANG SEMU PISANG (Musa paradisiaca L.) SEBAGAI SUMBER BELAJAR UNTUK MATERI PERTUMBUHAN DAN PERKEMBANGAN - Dian Dian (Horizon, 2021)
Pseudo banana stems can be used as a pot for planting spinach, because it contains with moisture content of ± 96.2 %. Spinach in its infancy requires considerable water. Requirements for success in the cultivation of spinach on banana pseudo stem pots is planting media. The composition of the planting media of topsoil, sand, and husk charcoal used contains nutrients that might suit the needs of spinach extracted. This research is closely related to the learning of biology at school in the matter of growth and development. The purpose of this study was to determine the response of spinach’s growth to various kinds of planting media by using pseudo banana stem pots and produce a valid LKPD as a learning resource for growth and development material. Experimental research uses a completely randomized design (RAL), consisting of 5 treatments and 5 repetitions. The parameters observed were stem height, number of leaves, and wet weight of the plant. Data analysis using F test at α level of 5%. If there is influence continued with LSD or DNMRT test at α level of 5%. LKPD development research uses four-D models to the Develop stage which is at the validity stage. Analysis of the data used is quantitative analysis. The results showed that the response of spinach spinach growth to several kinds of growing media using pseudo potted stem pots of banana gave a significant effect on stem height and number of leaves. The best growing media for growth of spinach plants pulling out on banana pseudo stem pots is 100% humus soil. LKPD that was developed in the matter of growth and development is categorized as very valid in the aspects of content worthiness, linguistic, presentation, and graphic.